AN INSIGHT INTO SOLUBILITY AND SELECTIVITY OF H2S/CO2 IN CHOLINIUM-BASED AMINO ACID IONIC LIQUIDS FROM MOLECULAR DYNAMICS SIMULATION - MOHD SALEHIN, FITRI NORIZATIE (2020)
Ionic liquids (ILs) are molten salts with melting point below 100℃. They are highly desirable due to its distinctive physico-chemical properties and are widely used in many applications such as in catalysis, electrochemistry, and gas capture. The non-volatility of these salts is one of the important reasons why ILs are being explored for gas capture. Molecular dynamics (MD) simulation is one of the techniques to predict molecular properties of ILs that contributes to gas solubility. In this work, solvation free energies of H2S and CO2 in six cholinium-based amino acids ([Chl][AA]) ILs were computed using Bennet Acceptance Ratio (BAR) method employed in MD simulation. Prior to free energy simulation, the Optimized Potential for Liquid Simulation (OPLS) force fields were successfully validated.